HPLC-based Measurement of Glycated Hemoglobin using Dried Blood Spots Collected under Adverse Field Conditions. (2nd January 2018) - Thomas, Duncan; Seeman, Teresa; Potter, Alan; Hu, Peifeng; Crimmins, Eileen; Herningtyas, Elizabeth Henny; Sumantri, Cecep; Frankenberg, Elizabeth
ABSTRACT: Glycated hemoglobin (HbA1c) measured using high-performance liquid chromatography (HPLC) assays with venous blood and dried blood spots (DBS) are compared for 143 paired samples collected in Aceh, Indonesia. Relative to gold-standard venous-blood values, DBS-based values reported by the HPLC are systematically upward biased for HbA1c<8% and the fraction diabetic (HbA1c ≥ 6.5%) is overstated almost five-fold. Inspection of chromatograms from DBS assays indicates the % glycosylated calculated by the HPLC excludes part of the hemoglobin A which is misidentified as a hemoglobin variant. Taking this into account, unbiased DBS-based values are computed using data from the machine-generated chromatograms. When the DBS are collected in a clinic-like setting, under controlled humidity/temperature conditions, the recalculated values are almost identical to venous-based values. When DBS are collected under field conditions, the recalculated values are unbiased, but only about half the HbA1c values are measured reliably, calling into question the validity of the other half. The results suggest that collection conditions, particularly humidity, affect the quality of the DBS-based measures. Cross-validating DBS-based HbA1c values with venous samples collected under exactly the same environmental conditions is a prudent investment in population-based studies.